What drives household labor absorption in Indonesia? A provincial-level analysis using panel ARDL modeling - Vivi Silvia; Maulidar Agustina; Dian Zulfa (Cogent Economics & Finance)
Labor absorption is a persistent challenge in Indonesia, particularly within the MSME sector, which plays a vital role in employment generation. However, existing research has largely overlooked the influence of household spending and financial access on labor absorption, as well as the mediating mechanisms that connect these factors. Addressing these gaps, this study investigates how household spending, working capital credit, and the number of MSME units affect labor absorption in Indonesia, focusing on their relationship with spending on labor and MSME output value, using panel Autoregressive Distributed Lag (ARDL) modeling across 34 provinces from 2013 to 2023. The results show that, in the long term, household spending, working capital credit, labor spending, and the number of MSME units significantly enhance labor absorption, while MSME output value has no direct effect. Household spending fully mediates the relationship between MSME output and labor absorption, while other relationships show partial mediation. In the short term, the relationships are less stable due to adjustments toward equilibrium. Policy implications highlight boosting household purchasing power, improving credit access, and supporting MSME growth to enhance job creation. Recommendations include lowering interest rates, providing workforce training, encouraging innovation, and evaluating policies to strengthen employment opportunities.